A Canadian model for providing high-quality, timely and relevant evidence to meet health system decision-maker needs: the SPOR Evidence Alliance - Wasifa Zarin; Carole Lunny; Sabrina Chaudhry; Sonia M. Thomas; Annie LeBlanc; Fiona Clement; Ahmed M. Abou-Setta; Janet A. Curran; Brian Hutton; Ivan D. Florez; Linda C. Li; Stephen Bornstein; et al. (Canadian Science Publishing, 2022)
Canada has made great progress in synthesizing, disseminating, and integrating research findings into health systems and clinical decision-making; yet gaps exist in the research-to-practice continuum. The Strategy for Patient-Oriented Research (SPOR) Evidence Alliance aims to help close gaps by providing decision-makers with evidence that is timely, context sensitive, and demand driven to better inform patient-oriented practices and policies in health systems. In this article, we introduce a model established in Canada to support decision-maker needs for high-quality evidence that is patient oriented to enhance health systems performance. We provide an overview of how this model was implemented, who is involved, who it serves, as well as its organizational structure and remit. We discuss key milestones achieved to date and the impact this initiative has made within the health research community. The strength of the SPOR Evidence Alliance lies in its unique ability to simultaneously: (i) serve as a national platform for researchers to stay connected and collaborate to minimize duplication of efforts and (ii) facilitate access to research knowledge for patient partners and decision-makers. In doing so, the SPOR Evidence Alliance is supporting health policy and practice decisions that support and strengthen Canada's dynamic health systems.